A Marine Tourism Management Model Based on Community-Based Tourism and Its Role in Increasing The Income of Coastal Communities in Balikpapan City - Markhamah, Siti; Soesilowati, Etty; Rahmawati, Farida (PT. EQUATOR SINAR AKADEMIA, 2024)
This study aims to describe the management of community-based tourism in the coastal area of Balikpapan City, analyze the suitability between the assessment of interests and expectations of the community towards the implementation of CBT dimensions, and determine the effect of marine tourism development on increasing the income of coastal communities. Data analysis was conducted using Quantitative Descriptive Analysis, Importance-Performance Analysis, and Multiple Regression Analysis. The results show that the management of community-based marine tourism in the coastal area of Balikpapan City is generally in the good category. Multiple linear regression analysis shows that CBT-based marine tourism has a significant influence on increasing the income of coastal communities. Practical suggestions include increasing the protection and conservation of coastal ecosystems through the involvement of visitors and coastal communities, as well as involving the community more in tourism-related policy making